2013
DOI: 10.1111/bjd.12569
|View full text |Cite
|
Sign up to set email alerts
|

Increased epicardial fat tissue is a marker of subclinical atherosclerosis in patients with psoriasis

Abstract: We demonstrated that EFT and CIMT are increased in patients with psoriasis, and that echocardiographic EFT is closely correlated with CIMT in patients with psoriasis. The echocardiographic assessment of EFT may have the potential to be a simple marker of subclinical atherosclerosis and increased cardiovascular risk in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…In this study, the ratio of the presence of CAC was also significantly high in younger psoriatic patients. Clinical aspects, such as PASI score, hypertension and smoking habit, were not associated with EAT or CAC score, in agreement with previous reports …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the ratio of the presence of CAC was also significantly high in younger psoriatic patients. Clinical aspects, such as PASI score, hypertension and smoking habit, were not associated with EAT or CAC score, in agreement with previous reports …”
Section: Discussionsupporting
confidence: 92%
“…Epicardial adipose tissue functions as a paracrine organ by releasing bioactive adipocytokines into the adjacent interstitium of the myocardium and coronary arteries, and may represent cardiovascular risk . Recent studies have shown significantly higher EAT volume in psoriatic patients compared with control subjects, and EAT was independently associated with the presence of CAC . There is a correlation between EAT and BMI or metabolic syndrome, but Japanese psoriatic patients comprise only 0.34% of the population, with metabolic syndrome and obesity generally much less prevalent than Caucasians .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated associations between EFT and CVD, insulin resistance, coronary calcium score, and metabolic syndrome [13,36]. Previous studies have also reported that psoriatic patients had higher EFT values [16,37]. The present study found higher EFT values in psoriatic patients than in healthy controls, which agrees with the results of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, the authors demonstrated that EFT is increased in patients with psoriasis, and that echocardiographic EFT is closely correlated with surrogate inflammatory markers such as carotid intima media thickness in patients with psoriasis [10]. The echocardiographic assessment of EFT may have the potential to be a simple marker of subclinical atherosclerosis and increased cardiovascular risk in patients with psoriasis [10]. …”
mentioning
confidence: 99%